Scenario of Educational Management for Unity and Peace in ASEAN Community: Research Utilization (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Educational management for unity and peace of countries in ASEAN community was focused on this researcharticle. The purpose was to propose scenario and strategy of educational management for unity and peace in ASEANcommunity. Ethnographic Delphi Future Research (EDFR) was used for research design, and the target group was educationalpersonnel from ten ASEAN countries. Research tools were interview schedule and questionnaires. Qualitative data wereanalyzed using content analysis and analytic induction, and quantitative data were analyzed using descriptive statistics. Resultsindicated that six strategies of educational management were set for unity and peace of countries in ASEAN community whichwere to develop teachers and administrators, to collaborate curriculum and assessment, to enhance teaching and instruction, toencourage educational research, to facilitate educational opportunity, and to develop educational management. The analyzedresult from Ethnographic Delphi Future Research technique showed that 6 strategies and 26 goals have been accepted with theconsensus from experts all items. Each item showed the median of strategies and goals were between 4.00 to 5.00, the absoluteof median and mode difference was 0 in all items, interquartile range were between 0.00 – 1.00 which can be explained that theexpert group had correlated agreement on ASEAN education strategic plan. Research results for scenario of educationalmanagement for unity and peace in ASEAN Community was being used for the speech at two international conference as akeynote speech